A 54‐year‐old healthy patient with meningitis and conjunctivitis - Gilles Troché; Amandine Henry; Florence Sarfati; Charles Hickel; Marlène Amara; Fabrice Bruneel (Journal of the American College of Emergency Physicians Open)
Abstract We describe a case report of hypermucoviscous Klebsiella pneumoniae (KP) promptly diagnosed by blood and cerebrospinal fluid (CSF) culture with positive string test. The patient, without medical history, developed in a few hours multiple localizations, typical of hypervirulent KP. Combination of multiple typical localizations (eye, CSF, pulmonary, hepatic) and string test enabled rapid diagnosis of hypermcoviscous and hypervirulent KP.